Methemoglobinemia after injection of prilocaine for pre-medication of circumcision - Yılmaz Tabel (Dicle Medical Journal, 2009)
Methemoglobinemia may occur in congenital and acquired circumstances. Acquired methemoglobinemia occurs in individuals exposed to a various of agents. Prilocaine is a local anesthetic agent that is widely used in clinical practice, but as well usage at treatment dosage in infancy can cause methemoglobinemia. We report an infant who became methemoglobinemia after injection of prilocaine and spontaneous recovery with supportive treatment.